2023
DOI: 10.1021/acs.jpclett.3c01723
|View full text |Cite
|
Sign up to set email alerts
|

Interpolating Nonadiabatic Molecular Dynamics Hamiltonian with Bidirectional Long Short-Term Memory Networks

Bipeng Wang,
Ludwig Winkler,
Yifan Wu
et al.

Abstract: Essential for understanding far-from-equilibrium processes, nonadiabatic (NA) molecular dynamics (MD) requires expensive calculations of the excitation energies and NA couplings. Machine learning (ML) can simplify computation; however, the NA Hamiltonian requires complex ML models due to its intricate relationship to atomic geometry. Working directly in the time domain, we employ bidirectional long short-term memory networks (Bi-LSTM) to interpolate the Hamiltonian. Applying this multiscale approach to three m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 42 publications
(62 reference statements)
0
4
0
Order By: Relevance
“…Our group has recently demonstrated that the computational cost of NAMD can be reduced by interpolating the NAMD Hamiltonian along an MLFF trajectory. [40][41][42][43] In this work, we report a multiscale methodology and study the coupled structural evolution and quantum dynamics of charge carriers in dual defect ON-GCN over a nanosecond timescale by combining NAMD and real-time time-dependent density functional theory (RT-TDDFT) with supervised ML learning. We train an MLFF to investigate structural changes in dual defect ON-GCN over nanosecond MD trajectories, revealing hydrogen hopping involving four tautomeric structures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our group has recently demonstrated that the computational cost of NAMD can be reduced by interpolating the NAMD Hamiltonian along an MLFF trajectory. [40][41][42][43] In this work, we report a multiscale methodology and study the coupled structural evolution and quantum dynamics of charge carriers in dual defect ON-GCN over a nanosecond timescale by combining NAMD and real-time time-dependent density functional theory (RT-TDDFT) with supervised ML learning. We train an MLFF to investigate structural changes in dual defect ON-GCN over nanosecond MD trajectories, revealing hydrogen hopping involving four tautomeric structures.…”
Section: Introductionmentioning
confidence: 99%
“…Our group has recently demonstrated that the computational cost of NAMD can be reduced by interpolating the NAMD Hamiltonian along an MLFF trajectory. 40–43…”
Section: Introductionmentioning
confidence: 99%
“…The trajectory analysis requires ab initio molecular dynamics (AIMD) or, alternatively, interatomic potentials or tight-binding DFT (TBDFT) methods. Fortunately, recent machine learning (ML) techniques have been implemented in NAMD simulations. ML models may overcome the computational time scale limitation, especially in large systems composed by thousands of atoms. Furthermore, the analysis of excitation energies requires TDDFT calculations over each one of the systems collected in the trajectory and also contributes to the computational increase.…”
Section: Introductionmentioning
confidence: 99%
“…Ab initio molecular dynamics (AIMD) are used to determine how atoms move over time, but AIMD is computational demanding which imposes limits on the size of models studied. One potential way to address this problem is by combining AIMD simulations and machine learning to generate machine learned force fields (MLFFs). , Large and accurate data sets are used to construct traditional MLFFs; therefore, there is a lot of trial and error involved in parameter optimization and data selection . Generating on-the-fly MLFF through active learning schemes gives the advantage that no prior training is required and the on-the-fly force fields are generated automatically during the AIMD simulation. , Using this approach, the results can be achieved with the accuracy of AIMD while also speeding up the simulation .…”
Section: Introductionmentioning
confidence: 99%